Lipophilicity-dependent ruthenium N-heterocyclic carbene complexes as potential anticancer agents. Issue 16 (23rd March 2015) - Lv, Gaochao; Guo, Liubin; Qiu, Ling; Yang, Hui; Wang, Tengfei; Liu, Hong; Lin, Jianguo
Abstract : Five novel Ru(ii )–N-heterocyclic carbenes (NHC) were synthesized and biologically evaluated, one of which showed superior activity against PC-3 cell lines and 6 fold more activity than cisplatin. Abstract : Five Ru(ii )–N-heterocyclic carbenes (NHC) (1–5 ) were synthesized by reacting the appropriately substituted imidazolium chlorides with Ag2 O, forming the NHC-silver chloride in situ followed by transmetalation with dimeric p -cymene ruthenium(ii ) dichloride. All the complexes were characterized by NMR and ESI-MS, and complex1 was also characterized by single-crystal X-ray diffraction. The IC50 values of these five complexes were determined by the MTT-based assay on four human cancer cell lines, SKOV-3 (ovarian), PC-3 (prostate), MDA-MB-231 (breast) and EC109 (esophagus). The cytotoxicities of these complexes changed from a moderate effect to a fine one, corresponding to the increasing lipophilicity order of the complex of2 <1 <3 <4 <5 (0.91, 0.88, 1.36, 1.85 and 2.62 for1–5 respectively). Complex5 showed the most cytotoxicity with the IC50 values 10.3 ± 0.3 μM for SKOV-3, 2.9 ± 0.1 μM for PC-3, 8.2 ± 0.6 μM for MDA-MB-231, 6.4 ± 0.2 μM for EC109 cell lines. Due to the superior cytotoxicity of complex5 against the PC-3 cell lines, further biological evaluations were carried out to elucidate its action mechanism. The morphologic changes and cell cycle analysis showed that complex5 can inhibit PC-3 cell lines by inducing cell cycle arrest at the G2/M phase. The DNA binding experiments further demonstrate that complex5 has a better binding ability for DNA ( K b = 2.2 × 10 6 M −1 ) than complexes1–4 (3.8 × 10 5, 7.0 × 10 5, 5.7 × 10 5, and 1.9 × 10 5 respectively).